Muslim-Hindu Cooperation in Addressing Social Problems in the Tengger Tribe in East Java, Indonesia - Dicky Nur Rahman; Moh. Hamim Assidiki; Iklil Nafisah; Moh. Ali Aziz (Jurnal Multidisiplin Madani, 2023)
This research aims to describe the cooperation between Muslim and Hindu communities in handling social problems in the Tengger Tribe, Mount Bromo area, East Java. Religious diversity among the Tengger people provides challenges and opportunities for solving complex social problems. Using symbolic interaction theory and descriptive-qualitative research methods, this study reveals several social problems, including interfaith marriages, lack of access to education, challenges in maintaining identity and tradition, and population administration issues. Interfaith marriage is considered normal in Tengger society, which is not in line with Islamic teachings. Lack of access to education after junior high school is a barrier for the community. Population administration issues, such as birth registration and identity documents, also affect the Tengger community. This research found that there is strong cooperation between the Muslim and Hindu communities in addressing social problems. The contribution of this research is to provide an understanding of the importance of religion, culture, tolerance, and interfaith harmony in strengthening cooperation in solving social problems. The implication of this research is the importance of improving access to education, maintaining identity and tradition, and improving population administration to build a more harmonious and inclusive society in Indonesia